STRUCTURAL AND DYNAMIC PROPERTIES OF MUTANTS OF THE SOD1 PROTEIN ASSOCIATED WITH AMYOTROPHIC LATERAL SCLEROSIS - N. A. Alemasov; N. V. Ivanisenko; V. A. Ivanisenko (Вавиловский журнал генетики и селекции)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease, which affects motor neurons in the brain and spinal cord and leads to patients’ death. One of the causes of motor neuron degeneration and death is the formation of intracellular protein aggregates formed by a mutant SOD1 protein. Recently, it has been shown that the survival time of ALS patients with specific mutation in SOD1 gene inversely correlates with thermodynamic stability of the SOD1 mutant protein. In the present paper, we hypothesize that mutant SOD1 aggregation can be facilitated by not only destabilization due to hydrogen bonds disruption but also by formation of new hydrogen bonds, which can stabilize intermediate “pathogenic” conformations of the mutant SOD1 protein. Molecular dynamics simulations were conducted to estimate frequencies of hydrogen bond occurrence in the protein structure. It was shown that the regression model based on frequencies of hydrogen bond occurrence significantly better correlated with patients’ survival time (R = 0.89, p < 0.00001) than the estimation based on thermodynamic stability analysis of mutant SOD1 proteins.